2010
DOI: 10.1007/s10533-010-9495-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and partitioning of mercury in a river catchment impacted by former mercury mining activity

Abstract: Mercury distribution and partitioning was studied in the River Idrijca system, draining the area of the former Idrija mercury mine, Slovenia. Mercury dynamics were assessed by speciation analysis of mercury in water and river bed sediment samples during a 2-year study at locations on the River Idrijca and its major tributaries. Simultaneously, the influence of some major physico-chemical parameters that influence the fate of mercury in the aquatic environment was investigated. The distribution of mercury speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The Idrijca River in Slovenia drains the area of the Idrija Hg mine, now closed but formerly the world's second largest Hg mine. Five sampling locations were selected along the Idrijca River (Figure 7), representative of different levels of Hg impact as determined by previous studies [15,[35][36][37][38][39]. The first location, above the Belca inflow, is a pristine site with very low Hg contamination, while all the downstream sampling sites are affected by the Hg mine to some extent [36].…”
Section: Application Of the Ethylation Methods To The Determination Ofmentioning
confidence: 99%
“…The Idrijca River in Slovenia drains the area of the Idrija Hg mine, now closed but formerly the world's second largest Hg mine. Five sampling locations were selected along the Idrijca River (Figure 7), representative of different levels of Hg impact as determined by previous studies [15,[35][36][37][38][39]. The first location, above the Belca inflow, is a pristine site with very low Hg contamination, while all the downstream sampling sites are affected by the Hg mine to some extent [36].…”
Section: Application Of the Ethylation Methods To The Determination Ofmentioning
confidence: 99%
“…The geochemistry of Hg has been extensively investigated (UIIrich et al, 2001;Kocman et al, 2011) and its global biogeochemical cycle is well characterized. The impact of Hg environmental contamination on human health has also attracted much scientific attention, originally directed to large-scale industrial releases or agricultural applications (Gochfeld, 2003;Kobal et al, 2004Kobal et al, , 2008.…”
Section: Populatíon-related Variablesmentioning
confidence: 99%
“…It has been demonstrated that Hg contamination in the Gulf of Trieste mostly originates from riverine inputs of the Isonzo/Soča River e.g., [19,22,23] draining Hg-enriched river banks and floodplain deposits along the river basin hosting the second largest Hg mine worldwide [24][25][26]. Indeed, over 500 years of cinnabar (HgS) extraction activity at the Idrija mining district (western Slovenia, Figure 1) has led to Hg contamination of multiple environmental matrices both in the areas surrounding the mine and far from this primary source [24,25,[27][28][29]. the world-wide natural background (0.03 µg•g −1 ) [15] due to both natural and anthropogenic sources.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most contaminated areas in Italy, the Venice Lagoon, the Marano and Grado Lagoon and the Gulf of Trieste are located in the northern area of the Adriatic Sea [16][17][18][19][20] where marine sediments showed the highest amount of Hg (0.05-8.63 µg•g −1 , [21]), diminishing towards the central and southern sector of the same basin [21]. It has been demonstrated that Hg contamination in the Gulf of Trieste mostly originates from riverine inputs of the Isonzo/Soča River e.g., [19,22,23] draining Hgenriched river banks and floodplain deposits along the river basin hosting the second largest Hg mine worldwide [24][25][26]. Indeed, over 500 years of cinnabar (HgS) extraction activity at the Idrija mining district (western Slovenia, Figure 1) has led to Hg contamination of multiple environmental matrices both in the areas surrounding the mine and far from this primary source [24,25,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%